2020
DOI: 10.1016/j.yjmcc.2020.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Apelin-potential therapy for COVID-19?

Abstract: We believe that, in parallel to the attempts for direct blockade of the SARS-CoV-2 penetration into host cell and repurposing drugs, finding new therapeutic strategies for patients with lung injury or cardiovascular complications/coagulopathies associated with COVID-19 should be paid particular attention. Apelin or its receptor agonists are of great potential treatment for COVID-19 through suppressing angiotensin-converting enzyme (ACE) and angiotensin II (Ang-II) production, as well as, down-regulating angiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…Our previous published work demonstrated that Ang II-induced inflammation, oxidative stress, cardiorenal fibrotic remodeling and dysfunction were exacerbated in ACE2-deficient mice [ 21 , 22 ]. Besides, apelin has been demonstrated to protect against acute respiratory distress syndrome, cardiovascular injury and endothelial inflammation through activating the ACE2/Ang-(1–7)/Mas axis and blocking the Ang II-AT1R actions, indicating that apelin/ACE2 signaling could be a promising therapeutic target in ameliorating cardiorenal injuries during COVID-19 [ 23 ]. In this study, we demonstrated decreased apelin-ACE2 signaling and increased levels of pro-inflammatory factors and fibrosis-related genes in post-MI HF rats, AKI and ACE2 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous published work demonstrated that Ang II-induced inflammation, oxidative stress, cardiorenal fibrotic remodeling and dysfunction were exacerbated in ACE2-deficient mice [ 21 , 22 ]. Besides, apelin has been demonstrated to protect against acute respiratory distress syndrome, cardiovascular injury and endothelial inflammation through activating the ACE2/Ang-(1–7)/Mas axis and blocking the Ang II-AT1R actions, indicating that apelin/ACE2 signaling could be a promising therapeutic target in ameliorating cardiorenal injuries during COVID-19 [ 23 ]. In this study, we demonstrated decreased apelin-ACE2 signaling and increased levels of pro-inflammatory factors and fibrosis-related genes in post-MI HF rats, AKI and ACE2 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, beyond the RAAS and KKS, ACE2 has been shown to act on other substrates such as apelin-13/17, neurotensin (1-11), β-casomorphin-(1-7), dynorphin A (1-13), and ghrelin among others [86]. These substrates are interesting potential therapeutic targets for COVID-19 [77], but we will not discuss them because their involvement in COVID-19 is still highly speculative.…”
Section: Ace2 As a Target For A Sars-cov-2 Therapeutic Strategymentioning
confidence: 99%
“…These observations may lead to the conclusion that ACE2 down‐regulation in COVID‐19 increases the concentration of higher‐affinity parental apelin peptides, countering the effects of the aggressive branch of the RAAS. Indeed, exogenous administration of apelin has been suggested as a treatment for COVID‐19 27 . However, even though parental apelins have a higher affinity for APJ than metabolised apelins, there is an increasing volume of research suggesting that parental apelin isoforms induce receptor internalisation mediated by β‐arrestin signalling, blunting the effect of high concentrations of parent apelin peptides.…”
Section: Ace Vs Ace2 In Raas‐related Events In Covid‐19mentioning
confidence: 99%